The Role of AI-Powered Platforms in English Education - Choriyeva Guzal (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Innovation in education is reshaping the way learners acquire knowledge and teachers deliver instruction. This paper explores the integration of science and innovation in the education system, focusing specifically on the role of AI-powered platforms—Grammarly, ChatGPT, and Elsa Speak—in English language learning. Drawing on empirical evidence and secondary sources, the study highlights how these tools enhance writing accuracy, speaking fluency, and pronunciation skills. Using a descriptive and analytical design with 50 undergraduate participants, the research demonstrates that AI tools provide immediate feedback, foster learner autonomy, and reduce teacher workload while requiring guided instructional support. The findings contribute to ongoing discussions on how scientific and technological innovations can sustainably transform language education.